Smart Factories for Mass Individualization - Xi Gu; Yoram Koren (Encyclopedia, 2024)
With the rise of individualism as a social trend and the wide use of the Internet and social media, today’s customers increasingly want to design and build unique products that fit their individual preferences and needs. Mass individualization is defined as a manufacturing paradigm that aims to produce individualized products cost-effectively. This paradigm differs from the previous paradigms in which the manufacturing company designed and manufactured the products, and the customer chose a product. In the mass individualization paradigm, the customers will be actively involved in product design, and the manufacturer will produce a unique product for each customer at a reasonable cost and of reliable quality. Due to the need for smooth communication and interactions between the buyer and the factory, new factories for individualized products will be located near potential buyers, which will have a significant impact on local economies. This entry explores the relationship between mass individualization and other emerging manufacturing paradigms and concepts in the Industry 4.0/5.0 era, and discusses how smart factories can improve manufacturing efficiency and facilitate the realization of the mass individualization paradigm.